Karakteristik Biologi dan Preferensi Pakan Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Berbagai Jenis Pakan - Hidayah, Vania Utami; Afifah, Lutfi; Surjana, Tatang; Subagyo, Vani Nur Oktaviany (AGRICA, 2024)
Fall Armyworm (Spodoptera frugiperda) is one of the invasive insect species that cause yield loss in corn crops. This pest can attack other crops, such as food crops, vegetables, legumes, and weeds. This research aims to determine the host suitability of S. frugiperda on several types of host plants. The method used was an experimental method with a single-factor completely randomized design (CRD) consisting of four treatments in five replications using four different types of host plants: maize (Zea mays L.), soybean (Glycine max L.), papaya (Carica papaya L.), and chinese kale (Brassica oleraceae var. acephala). The highest percentage of S. frugiperda attack intensity in the choice test was obtained in the treatment with chinese kale leaves (70%) and the lowest in the papaya leaves treatment (20%). In the feeding activity of 3rd instar larvae, the treatment of maize leaves and soybean leaves showed the fastest feeding activity at 11:00 and 12:00, while in the feeding activity of 4th instar larvae, the treatment of maize leaves and chinese kale leaves showed a fast larval feeding activity with a feeding duration of ± 5-10 minutes. Fall Armyworm can also attack other host plants such as soybeans and chinese kale. It can even endure by feeding on papaya leaves, which are typically used as a botanical pesticide. It is essential to step up surveillance against this pest because there are so many additional possible hosts for it.